Evaluation Of Anti -Ulcer Activity of Alcoholic Extract of Hibiscus Rosa Sinesis In Rats. - T, Deshmukh M.; V, Shete R.; T, Deshmukh V.; R, Borate S.; B, Nagul (Asian Journal of Pharmaceutical Research and Development, 2013)
Gastric ulcers the most wide state disease and are a very common global problem today. Peptic ulcer is a lesion of the gastric/duodenal mucosa occurs at a site where the mucosal epithelium is exposed to acid and pepsin. As plants are a rich source of active principles and antioxidants, there has been a growing interest to identify and scientifically validate agents that have traditionally been used in folk medicine in the treatment of gastric ulcers and related diseases. Hibiscus Rosa-Sinensis a well known member of the family Malvaceae, Hibiscus rosa-sinensis grows as an evergreen herbaceous plant. H. rosa sinensis has been used for the treatment of a variety of diseases. Traditional uses of this plant are refrigerant" emollient and emmenagogue, aphrodisiac; decoction given in bronchial catarrh; infusion of petals is a refrigerant drink in fever, demulcent in cough and useful in strangury, cystitis and other genito-urinary troubles. In this experiment positive control group ligation of pylorus showed increase in gastric juice, ulcer index, pH of gastric juice and fee acidity. Administration of Ranitidine (30mg/kg), HAHR (100& 200 mg/kg) showed significant reduction with respect to above parameters and showed significant increase in % gastroprotection. In present study HAHR significantly reduced the gastric acid secretion. The cyto-protective action which promotes the generation of prostaglandin and causes decreases in secretion of gastric acid, mixture significantly reduced the gastric ulceration in pyloric ligated rats without affecting the gastric secretion or pepsin. Phytochemical examination revealed that HAHR contains saponins, sterols and flavonoids. Saponins, sterols and flavonoids present in HAHR may be responsible for antiulcer activity in pylorus induced ulcer model.